Strategi Komunikasi Pemulihan Pasca Krisis Menggunakan Influencer oleh KemenKopUKM - Tito, Fitara; Noer, Mochammad Kresna (P3M Politeknik Negeri Media Kreatif, 2025)
The digitalization era has brought significant changes in how communication is conducted, especially during crises. One of the challenges faced is how the government handles crises that affect public reputation. This study aims to analyze the crisis communication strategies employed by the Ministry of Cooperatives and SMEs (KemenKopUKM) in managing crises through the use of influencers. The theories utilized in this research are the Social-Mediated Crisis Communication (SMCC) theory and crisis communication theory, which explain how communication mediated through social media can repair damaged public images. The methodology used is a qualitative approach with an in-depth case study design, accompanied by content analysis to examine the meaning of messages conveyed through social media. Data is collected through in-depth interviews with the KemenKopUKM communication team and involved influencers, as well as an analysis of relevant documents. The operationalization of concepts involves identifying key indicators of crisis communication and the effectiveness of using influencers in the repair process.